2021
DOI: 10.1186/s13643-021-01592-x
|View full text |Cite
|
Sign up to set email alerts
|

Technology-based health solutions for cancer caregivers to better shoulder the impact of COVID-19: a systematic review protocol

Abstract: Background Cancer patients are particularly vulnerable to COVID-19, partially owing to their compromised immune systems and curbed or cut cancer healthcare services caused by the pandemic. As a result, cancer caregivers may have to shoulder triple crises: the COVID-19 pandemic, pronounced healthcare needs from the patient, and elevated need for care from within. While technology-based health interventions have the potential to address unique challenges cancer caregivers face amid COVID-19, limi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Technology can also assist clinicians in connecting with patients when in-person medical visits are difficult or dangerous (eg, in rural settings, following natural disasters). 86 Overall, telemedicine and other technology-based interventions have the potential to provide a comprehensive range of benefits 52 that should be sufficiently, if not fully, explored particularly in times of crises and catastrophes. 87 In addition to addressing imminent and relevant social emergencies, s our overarching research ( figure 2 ) could also inform policymaking on the use and application of technology-based interventions across nursing homes amid the pandemic and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…Technology can also assist clinicians in connecting with patients when in-person medical visits are difficult or dangerous (eg, in rural settings, following natural disasters). 86 Overall, telemedicine and other technology-based interventions have the potential to provide a comprehensive range of benefits 52 that should be sufficiently, if not fully, explored particularly in times of crises and catastrophes. 87 In addition to addressing imminent and relevant social emergencies, s our overarching research ( figure 2 ) could also inform policymaking on the use and application of technology-based interventions across nursing homes amid the pandemic and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…The first research stage was where we accidentally encountered the conceptualization issue associated with the term technology-based interventions . Our initial research objective was to conduct a systematic review study on technology-based interventions for cancer caregivers [ 24 ]. During this process, we found that, although there is a rich body of research on technology-based interventions for cancer caregivers, most of the authors fail to offer a clear conceptualization of the term.…”
Section: Methodsmentioning
confidence: 99%
“…The emphasis on technology-based interventions for cancer caregivers has become particularly pronounced amid the COVID-19 pandemic, a global health crisis that has effectively crippled many, if not all, of the traditional health care services available to patients and caregivers [21][22][23]. During the pandemic, many cancer caregivers have found much-needed solace and support in technology-based health care services, ranging from online support groups to videoconferencing with patients or health care professionals [24][25][26]. It is important to note that there is a growing body of research investigating the benefits of technology-based health solutions [24][25][26][27][28][29].…”
Section: The Critical Role Of Technology-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, based on our pilot literature sample, such systematic evidence synthesis is still lacking. In particular, the existing review articles either focus on remote medical services for non COVID-19 conditions (eg, refs 24–32) or do not sufficiently elaborate on the implementation concepts 15 33–35. Moreover, to the best of our knowledge, structured literature synthesis has not been done with respect to the composition of the telemonitoring team.…”
Section: Introductionmentioning
confidence: 99%